(untitled) (Journal of Dhaka Medical College, 2017)
This cross sectional observational study was carried out in the department of Neurology, Dhaka Medical College and Hospital (DMCH), Dhaka, On 42 Patients of Amyotrophic Lateral Sclerosis (ALS) to find out their clinical and electrophysiological profiles, as well as to study the correlation between clinical presentation and electrophysiological findings. The mean age was found 44.64± 16.4 years. Majority of the patients were males.The mean duration of illness was found to be 1.33±0.53 Years and majority 35(83.3%) of the patients suffered from illness for 1- 2 years. Most 57.1% of the patients had upper limb onset, whereas 33.3% had lower limb onset and 9.5% had bulbar onset, muscle wasting, weakness and fasciculations were the most frequent presenting features. Clinically number of definite, probable and possible ALS cases were 4 (9.5%), 11 (26.2%) and 27 (64.3%) respectively. After doing electromyography, the definite cases increased 40(95.3%) significantly among which 29 cases did not have LMN features in e 3 regions clinically. Finally, this study reveals that the diagnostic yield is significantly higher with combine clinical and electrophyiological features compare to clinical feature alone for diagnosis definite ALS cases. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 65-72